Analisis Peranan Pasar Modal Dalam Mendukung Kebijakan Pemulihan Ekonomi Nasional Pasca Pandemi Covid 19 - Nadya Namora Hutabarat; Balqis Mawaddah Lubis; Vina Adelia; Akmal Pradana Nasution (Fakultas Ekonomi dan Bisnis Universita Labuhanbatu Sumatera Utara Indonesia, 2023)
The Covid-19 pandemic has greatly affected the economy throughout the world, including our country Indonesia. This condition also affects the sustainability of investment in the capital market. Many issuers sell their shares at a low value, reducing investor confidence in the capital market. Under these conditions, it is necessary to issue policies so that the Indonesian economy does not deteriorate. This research was conducted to determine the impact of the Covid -19 pandemic on the capital market and what policy regulations have been rolled out by the government and the Financial Services Authority.This research method uses various research studies of literature, namely the study of the form of research literature both in scientific journals, books, media articles, and statistical data. Literary research is a series of activities related to the collection, reading and recording and processing of library data. The research results obtained that the covid 19 pandemic had an impact on the Indonesian capital market which experienced a decline. The phenomenon of the covid-19 pandemic causes uncertainty in the future. This problem has a further impact on the decline in investment, social problems such as increasing unemployment and crime rates. This is of course not easy for every country to adopt policies to overcome the health crisis and economic recovery policies at the same time (Darmastuti et al. 2021).